MERUMUSKAN MODEL INTEGRASI MAQASID SYARIAH DALAM TATA KELOLA ZAKAT PRODUKTIF UNTUK TRANSFORMASI UMKM MUSTAHIK ACEH - Riski Maulana; Noufal Muksalmina (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Productive Zakat is a type of zakat provided as a resource to support individuals or groups, especially Micro, Small, and Medium Enterprise (MSME) actors who are in need. With this approach, it is hoped that the income of the mustahik (zakat recipients) can increase in the long term, ultimately impacting poverty reduction, particularly in the Aceh region. The organized management and distribution of productive zakat, guided by the principles of Maqasid Syariah (the objectives of Islamic law), is crucial to ensure the comprehensive and maximum impact of the program, especially in supporting the development of mustahik MSMEs in Aceh. The objective of this study is to develop an Integration Model of Maqasid Syariah in Productive Zakat Management to achieve social and economic transformation for mustahik MSMEs in the Aceh region. The study adopts a qualitative descriptive approach, focusing on field research and literature review. Primary data was collected through in-depth interviews with zakat managers (amil institutions) in Aceh, as well as aid recipients from mustahik MSME actors. Meanwhile, secondary data was obtained from a literature review on Maqasid Syariah, zakat management, and relevant reports on productive zakat programs in Aceh. The results of this research are expected to form a holistic model that assesses the impact of productive zakat not only from the perspective of increased income (net profit and capital growth) but also from the achievement of Maqasid Syariah aspects, such as protection of wealth (hifzh al-mal) and improvement of the quality of life (hifzh al-nafs) for the mustahik. The resulting model is also expected to serve as a reference for zakat institutions in Aceh to present more strategic productive zakat programs capable of bringing about better change in the future. Keywords: Integrated Productive Zakat, Maqasid Syariah, Mustahik MSMEs, Zakat Management, Social and Economic Transformation, Aceh.